Inisiasi, pertumbuhan, dan perkembangan kalus embriogenik tanaman stevia (Stevia rebaudiana) - Masna Maya SINTA; Rizka Tamania SAPTARI; . SUMARYONO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2021)
The leaves of sweetener plant Stevia rebaudiana contain secondary metabolites of steviol glycosides which are very sweet, with no calorie and zero glycemic index. Propagation of stevia by seeds is ineffective due to its low germination rate and diverse progenies. The tissue culture of stevia can be used to mass propagate rapidly and is commonly conducted by shoot multiplication. Up to now, the technology of somatic embryogenesis (SE) in stevia has not been successful yet. SE is developed to increase the production scale, rejuvenate clonal-propagated plants, and plant genetic transformation. The research objective was to develop protocols for the initiation, proliferation, and development of embryogenic calli of stevia as potential materials for SE. The explants used were young leaves, nodes, and internodes of axenic plantlets of stevia BX clone. The explants were cultured on MS solid media containing different concentrations of auxin and cytokinin for callus initiation. Callus emerged after 2-3 weeks of culture. The calli obtained were proliferated by subculturing several times as material stocks for indirect SE. MS solid media added with 1 µM 3,4-D and 16 mM CaCl2 gave the highest callus multiplication rate (4.7 times in 3 weeks). The selection of embryogenic calli was made continuously to obtain a pure line of embryogenic calli. Three types of calli attained were friable, fast-growing, yellowish calli, shiny nodular calli, and greenish nodular calli. Histological studies revealed that cells of the nodular calli had been differentiated to potentially formed somatic embryos.